Effect of cast part size on the microstructure and mechanical properties of a bainitic High-Carbon and High-Silicon Cast Steel (Fracture and Structural Integrity, 2024)
This study aims at assessing the impact of casting size on the bainitic transformation, resulting microstructures, and tensile properties of a high-carbon, high-silicon steel austempered at different temperatures. The casting size was analyzed by using Y blocks of two different thicknesses. The microsegregation, a common occurrence in cast parts, leads to different bainitic transformation rates at the microscopic scale. Specifically, interdendritic areas with higher alloying contents exhibit a slower transformation, resulting in a lower degree of transformation and a higher amount of blocky austenite. Despite differences in solidification structure and distribution of alloying elements, samples obtained from the thinner and thicker Y blocks yield comparable transformation times and mechanical properties, leading to enhanced uniformity in the mechanical behavior of the entire component. However, it is essential to ensure that the bainitic transformation is completed to minimize the detrimental effects of microsegregation in these cast steel components.The presence of very fine microstructures results in ultra-high strength with low ductility cast steel.
Keywords: cast part size; microsegregation; bainitic transformation; high-carbon high-silicon cast steel; mechanical properties